Data-driven analyses of human antibody variable domain germlines: pairings, sequences and structural features - Clarissa A. Seidler; Vera A. Spanke; Jakob Gamper; Alexander Bujotzek; Guy Georges; Klaus R. Liedl (mAbs)
The Observed Antibody Space provides the most abundant collection of annotated paired antibody variable domain sequences, thus offering a unique platform for the systematic investigation of the factors governing the pairing of antibody heavy and light chains. By examining a range of characteristics, including amino acid conservation, structural features, charge distribution, and interface residue identity, we challenge the prevailing assumption that pairing is random. Our findings indicate that specific physicochemical properties of single amino acid residues may influence the compatibility and affinity of heavy and light chain combinations. Further structural analyses based on antibody Fv fragments deposited in the Protein Data Bank (PDB) provide insights into the underlying structural features driving these pairing preferences, including a novel definition for the residues constituting the VH-VL interface, based on a collection of over 3500 structures. These results have significant implications for understanding antibody assembly and may guide the rational design of therapeutic antibodies with desired properties. Moreover, we provide a complete description and reference characterizing the various human germlines.